1982
DOI: 10.1159/000260595
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Striations in Carious Human Enamel

Abstract: A correlated microradiographic-transmission electron microscopic study examined incipient caries in human enamel from the enamel surface through the body of the lesion. In sections parallel to enamel prisms in the body of the lesion, cross-striations are accentuated as 3–4 μm wide, light and dark bands. In the more radiolucent striations, crystals are reduced in number as well as in length with some showing longitudinal splitting. In sections with prisms cut in cross-section, most crystals exhibit central diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

1983
1983
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
2
10
0
1
Order By: Relevance
“…3e). A similar mineral-rich band can be seen by TEM, together with a crystalfree gap (the prism junction) in the middle (see Simmelink and Nygaard, 1982, Fig. 6), and some crystals close to this gap have an unusual shape suggestive of remineralization.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…3e). A similar mineral-rich band can be seen by TEM, together with a crystalfree gap (the prism junction) in the middle (see Simmelink and Nygaard, 1982, Fig. 6), and some crystals close to this gap have an unusual shape suggestive of remineralization.…”
Section: Resultssupporting
confidence: 55%
“…Disclosure of the striae of Retzius arises from the strong demineralization of prism cross-striations in this plane,while, in between, striae of weaker intensity appear, formed from series of prism cross-striations having less mineral loss. Simmelink and Nygaard (1982) have identified prism cross-striations in TEM images. They have shown that at these points in carious enamel, there is a reduction in crystal length and number, and have evaluated possible reasons for this periodic susceptibility to acid.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown in a separate study (Takagi et al, 1984) that, while the lines of Retzius in a lesion are seen as continuous radiolucent bands in a contact microradiograph, the parallel beam microradiograph clearly shows that each band contains alternating radiopaque and radiolucent crossstriations. These appear to be akin to the striations perpen- dicular to the enamel prisms reported by Darling (1958) and by Simmelink and Nygaard (1982). This, again, shows that contact microradiographs provide information primarily on the mineral density of the specimen, and parallel beam microradiographs are capable of providing information on more detailed structural features of the specimen.…”
Section: Introductionsupporting
confidence: 63%
“…Unfortunately, the incorrect conclusion that enamel crystals are rectangular in cross section has led Warshawsky et al to criticize a paper I coauthored on enamel crystal dissolution in incipient caries (Simmelink and Nygaard, 1982). In that publication as well as in our earlier research on acid-treated enamel and precarious enamel (Swancar et al, 1971Simmelink et al, 1974), transmission electron microscopy showed a preferential dissolution of the center of enamel crystals (Fig.…”
Section: < +mentioning
confidence: 98%